2015
DOI: 10.1016/j.fob.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple binding modes of a small molecule to human Keap1 revealed by X‐ray crystallography and molecular dynamics simulation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 63 publications
1
47
2
1
Order By: Relevance
“…The binding affinity of AS with BSA was assayed using the SPR-based Biacore T200 (GE Healthcare) at 298 K 37,38. BSA was covalently immobilized on a CM5 gold sensor chip (GE Healthcare) by standard amine-coupling chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…The binding affinity of AS with BSA was assayed using the SPR-based Biacore T200 (GE Healthcare) at 298 K 37,38. BSA was covalently immobilized on a CM5 gold sensor chip (GE Healthcare) by standard amine-coupling chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…56 Babaoglu and Shoichet deconstructed a -lactamase inhibitor into fragments with 8, 11 and 14 heavy atoms and observed that the fragments did not preserve the binding mode corresponding to the same moiety in the full inhibitor. 57 Satoh et al 58 examples that fragments bound with appropriate overlap with the hot spot of consensus clusters preserve their binding mode, 65 while those bound at the site of other clusters may change their binding mode upon structure expansion. It is also consistent with the fact that although fragments are versatile binders with the ability to bind to various protein targets, they can also be evolved to higher specificity for the more druggable targets.…”
Section: Size and Shape Considerationsmentioning
confidence: 99%
“…The identification of Nrf2 activators has enticed the attention of researchers around the world as they can be utilized as therapeutic agents against oxidative stress‐related diseases. Two primary mechanisms elicit Nrf2 activation, one being the modification of cysteine residues in Keap1 and another being the disruption of protein‐protein interaction (PPI) between Keap1 and Nrf2 . In this study, we made an attempt to identify Keap1‐Nrf2 PPI inhibitors that disrupt PPI between Keap1a/b and Nrf2 in the zebrafish ( Danio rerio ) model system rather than identifying electrophilic activators, which covalently modify the cysteine residues in the Keap1.…”
Section: Introductionmentioning
confidence: 99%
“…Two primary mechanisms elicit Nrf2 activation, one being the modification of cysteine residues in Keap1 and another being the disruption of protein-protein interaction (PPI) between Keap1 and Nrf2. [15][16][17][18][19][20] In this study, we made an attempt to identify Keap1-Nrf2 PPI inhibitors that disrupt PPI between Keap1a/b and Nrf2 in the zebrafish (Danio rerio) model system rather than identifying electrophilic activators, which covalently modify the cysteine residues in the Keap1. The former is preferred the most due to their less toxic nature over the latter, as the latter modifies thiol groups of other off-target proteins leading to unpredictable toxic effects.…”
mentioning
confidence: 99%